Odpowiedzi

Najlepsza Odpowiedź!
2010-01-10T19:47:03+01:00
Metoda podstawiania
a)2x+3y=0,5
3x+y=-1

y=-1-3x
2x+3(-1-3x)=0,5
2x-3-9x=0,5
-7x=0,5+3
-7x=3,5/:(-7)
x=-1/2
y=-1-3*(-1/2)
y=-1+1,5

y=0,5
x=-0,5

b) 2x+y=14
8x+1/2y=35
y=14-2x
8x+1/2*(14-2x)=35
8x+7-1x=35
7x=35-7
7x=28/:7
x=4
y=14-2x
y=14-2*4
y=14-8

y=6
x=4

c) 3x+4y=2/*7
5x+7y=1/*(-4)

21x+28y=14
-20x-28y=-4

x=10
3*10+4y=2
30+4y=2
4y=-30+2
4y=-28/:4
y=-7
x=10

metoda przeciwnych współczynników
a) 2x+3y=0,5
3x+y=-1/(-3)

2x+3y=0,5
-9x-3y=3

-7x=3,5
x=-1/2
2x+3y=0,5
2(-1/2)+3y=0,5
-1+3y=0,5
y=1/2
x=-1/2

b)2x+y=14
8x+1/2y=35/*(-2)

2x+y=14
-16x-y=-70

-14x=-56/:(-14)
x=4
2x+y=14
8+y+14
y=14-8

y=6
x=4

c) 3x+4y=2 /*7
5x+7y=1/*(-4)

21x+28y=14
-20x-28y=-4

x=10
3*10+4y=2
30+4y=2
4y=-30+2
4y=-28/:4
y=-7
x=10

Mam nadzieje że pomogłam :):)
Pozdrawiam!!